Efeito de fertilizante foliar a base de extrato de algas e estresse hídrico na cultura da batata - Nunes, Gustavo Fonseca (2023)
Water stress is considered one of the main challenges in potato production, to ensure high productivity. In order to mitigate the effects of stress on plants, foliar fertilizers based on algae extract have been applied. The objective of this work was to evaluate the effects of different doses of foliar fertilizer based on algae extract on potato crop at different water depths. Two experiments were carried out simultaneously, one with the potato cultivar Ágata and the other with the potato cultivar Markies, in a greenhouse located at the Federal University of Uberlândia on the Monte Carmelo Campus in the year 2022. The design used was randomized blocks, in a 4 x 4 factorial scheme. The treatments resulted from the combination of four doses of foliar fertilizer based on algae extract (0 L ha-1, 0.5 L ha-1; 1.0 L ha-1; 4.0 L ha-1) and four irrigation depths (50%, 75%, 100% and 125% ETc), with three replications. Two potato varieties were used (Ágata and Markies). At 67 DAE, leaves were collected for nutritional analysis of macro and micronutrients and harvesting took place, where productive parameters were evaluated. After obtaining the data, ANOVA assumptions tests were performed. The data were submitted to analysis of variance by the F test (p<0.05), the means of the qualitative parameters were compared by the Tukey test (p<0.05). All analyzes were performed using R software. Leaf contents of P, K, Mg and Ca for cv. Ágata were below the recommended for the crop, regardless of irrigation depths and dose of foliar fertilizer based on algae extract. The B content was above the recommended and the Cu and Zn in the appropriate range for the two potato cultivars. The Mg content was adequate for the Markies variety up to irrigation depths of 75% of ETc. The foliar fertilizer based on algae extract promotes a reduction of the effects of water stress on the plants by increasing the amount of photon absorption by the Markies potato plants. Higher irrigation depths cause an increase in the number and weight of tubers in the special classes for cvs Ágata and Markies.